A More Comprehensive Climate Vulnerability Assessment Framework for Fisheries Social-Ecological Systems - Dudley, Peter N.; Rogers, Tanya L.; Morales, Mark M.; Stoltz, Amanda D.; Sheridan, Casey J.; Beulke, Anne K.; Pomeroy, Carrie; Carr, Mark H. (Frontiers in Marine Science, 2021)
Understanding and anticipating the effects of climate change on fisheries social-ecological systems (FSESs) is central to proactive fisheries management in a changing global climate. With fisheries management increasingly striving to consider interactions and feedbacks among people, targeted species, and the broader ecological and human communities, fisheries managers and participants need tools to help them assess these complex systems. We developed a new climate vulnerability assessment framework for analyzing the impacts of a climate-induced trend or event on a FSES. The framework divides the FSES into four interrelated and interacting domains: Ecological Community, Fished Species, Fishery, and Human Community. The framework provides a systematic approach to account for indirect as well as direct effects, links among subsystems, and multiple climate change-induced stressors. We demonstrate the framework’s utility by applying it to three case studies: the effects of a marine heatwave on the Dungeness crab FSES, the effects of a marine heatwave on the red sea urchin FSES, and the effects of long-term climate trends on North Pacific albacore. We found that the effects of a climatic trend or event on a FSES are often indirect and can trigger diverse and important feedbacks. These examples also showed that the climatic trend or event may cause changes in the temporal and spatial distribution of fishing effort and fished species that have a more significant impact on the FSES than changes to species abundance per se. Unlike other climate vulnerability assessment frameworks and applications, ours is designed to enable consideration of the range of feedbacks within and among both the ecological and human communities. As such, it is a valuable tool to guide the holistic examination and assessment of potential impacts to FSESs.